2019
DOI: 10.1212/wnl.0000000000008459
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4 is associated with younger age at ischemic stroke onset but not with stroke outcome

Abstract: Stroke outcome is determined by a complex interplay, where age and stroke severity are predominant predictors. Studies on hemorrhagic stroke indicate that APOE genotype is a predictor of poststroke outcomes, 1,2 but results from studies on ischemic stroke are more conflicting. 1,3 There is 1 study suggesting an influence of APOE genotype on age at ischemic stroke onset, 4 and sexspecific effects on outcome have been reported. 5 Taken together, there is a need for larger studies on APOE and ischemic stroke outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…When endophenotypes, such as stroke subtypes, are taken into account to assess allelic risk, the same pattern is observed, where ε2 promotes hemorrhages and ε4 promotes amyloid-β accumulation ( Sudlow et al, 2006 ). Some have suggested that the ε4 allele is only associated with an earlier onset of disease and not with disease severity both in CAA and stroke ( Greenberg et al, 1996 ; Lagging et al, 2019 ).…”
Section: Genetics Of Vascular Dementiamentioning
confidence: 99%
“…When endophenotypes, such as stroke subtypes, are taken into account to assess allelic risk, the same pattern is observed, where ε2 promotes hemorrhages and ε4 promotes amyloid-β accumulation ( Sudlow et al, 2006 ). Some have suggested that the ε4 allele is only associated with an earlier onset of disease and not with disease severity both in CAA and stroke ( Greenberg et al, 1996 ; Lagging et al, 2019 ).…”
Section: Genetics Of Vascular Dementiamentioning
confidence: 99%
“…This finding is consistent with a meta-analysis that found ApoE ε4 polymorphism to be associated with younger age at ischemic stroke onset. 42 The biology underlying this association in patients with stroke is uncertain, but might overlap with effects of this polymorphism in the setting of Alzheimer’s disease, where a single ApoE ε4 allele is associated with dementia age of onset that is 3.1 43 –8.8 44 years younger.…”
Section: Discussionmentioning
confidence: 99%
“…APOE-ε4, in particular, has been associated with late-onset AD [ 44 - 46 ]. Furthermore, several cardiovascular and neurological diseases have shown the involvement of APOE [ 47 - 50 ]. The different APOE confer variable risks to AD.…”
Section: Apolipoprotein E: Function and Role In Admentioning
confidence: 99%